2019
DOI: 10.1002/er.4632
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for municipal waste generation using artificial neural networks—Case study City of Zagreb, Croatia

Abstract: Summary The European Union's environmental legislation related to environmental protection, already implemented in the national legislation of the Republic of Croatia, aims to introduce a system of integrated and sustainable waste management. Within such a system, it is of utmost importance to have a better estimate of the amount of municipal waste generated, which directly influences future planning in the waste management sector. The aim of this research was to develop and optimize models for the estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Given that the mechanism of MSW generation is a very complex process and that there is a connection between socioeconomic factors and the generation of MSW, nonlinear regression models show greater accuracy than linear ones. Therefore, in recent times, the use of ANN in the prediction of waste generation is increasingly common, which also show better results [16]. Because of the above, no other mathematical models were used in this research, but only ANN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the mechanism of MSW generation is a very complex process and that there is a connection between socioeconomic factors and the generation of MSW, nonlinear regression models show greater accuracy than linear ones. Therefore, in recent times, the use of ANN in the prediction of waste generation is increasingly common, which also show better results [16]. Because of the above, no other mathematical models were used in this research, but only ANN.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, so far, many researchers have successfully applied ANN in MSW forecasting in their local area, and most MSW forecasting models are based on data from a specific region or data for a specific city. Thus, ANNs were also used to estimate the production of MSW in the city of Zagreb [16]. In the aforementioned research, a mathematical model was developed for estimating the production of MSW for the period from 2013 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WtE technologies and their application to treat MSW have been considered in the literature before 4,23‐25 . Kumar and Samadder 26 present a review of several WtE technologies and provide an assessment of various options for different income level countries.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted hydrogen production was in close agreement with the observed values from the experimental runs. Also Ribic et al 24 employed a MLP ANN to model municipal waste generation. The study revealed that the ANN model was robust in predicting municipal waste generation.…”
Section: Introductionmentioning
confidence: 99%